Orchestrated Testing: An Innovative Approach to a Multicenter Improvement Collaborative. (January 2017) - Pallotto, Eugenia K.; Chuo, John; Piazza, Anthony J.; Provost, Lloyd; Grover, Theresa R.; Smith, Joan R.; Mingrone, Teresa; Moran, Susan; Morelli, Lorna; Zaniletti, Isabella; Brozanski, Beverly
Health care quality improvement collaboratives implement care bundles to target critical parts of a complex system to improve a specific health outcome. The quantitative impact of each component of the care bundle is often unknown. Orchestrated testing (OT) is an application of planned experimentation that allows simultaneous examination of multiple practices (bundle elements) to determine which intervention or combination of interventions affects the outcome. The purpose of this article is to describe the process needed to design and implement OT methodology for improvement collaboratives. Examples from a multicenter collaborative to reduce central line–associated bloodstream infections highlight the practical application of this approach. The key components for implementation of OT are the following: (1) define current practice and evidence, (2) develop a factorial matrix and calculate power, (3) formulate structure for engagement, (4) analyze results, and (5) replicate findings.